Evaluasi Status Keberlanjutan Penggunaan Lahan di Das Ciliwung Bagian Hulu - Erwin Hermawan; Santun R.P Sitorus; Marimin Marimin; Suria Darma Tarigan (TATALOKA, 2020)
The Upper Ciliwung watershed is classified into 15 watersheds that must be restored. This study aims to evaluate the existing conditions of the sustainability status of land use based on environmental, economic and social aspects in the Upper Ciliwung Watershed Region. The Multidimensional Scaling technique through the development of the Rap-Watershed application was used to evaluate the Status of Sustainability of land use in the upstream Ciliwung watershed. The results of the study show that in general the identification of sustainable land use in each sub-watershed in the Upper Ciliwung watershed is categorized as moderately sustainable. The condition of the sub-watersheds in the Ciliwung Hulu watershed which is quite good in conditions that are sufficiently environmentally, economically and socially sustainable are the Upper Ciliwung watershed and the Cisarua watershed. The Cibalok sub-watershed and the Ciesek sub-watershed need to be considered specifically for the status of sustainability in the environmental and economic dimensions.